Potencial do manejo de Parapiptadenia rigida (Benth.) Brenan em sistema de alto fuste jardinado - Severiano, Camila Elizabete (2015)
The aim of this study was to evaluate the potential of the species P. rigida for the selection silvicultural system based on natural regeneration in a secondary Seasonal Deciduous Forest, and furthermore, to analyze its autoecological and synecological aspects. Studies were carried out on: vegetation structure, spatial point patterns, and furthermore, the association between mother-plant and regeneration, mother-plant and dispersed seed patches. Vegetation structure was evaluated through: importance value index - IVI% (horizontal structure) and natural regeneration by height class (vertical structure). Spatial pattern was evaluated through Ripley's K function (univariate and bivariate). The bivariate function is divided in two associations: 1) mother-plant and regeneration; 2) mother-plant and dispersion patches. In the floristic composition 766 trees were measured, in 18 botanical families, 31 genera and 34 species. The dominating species according to the vegetation analysis were, in decreasing order of the IVI% value: O. puberula, N. megapotamica, P. rigida, M. umbellata and C. vernalis. The univariate spatial point pattern for the species P. rigida was clustered. The spatial clusters showed attraction starting from 7.5 m of distance to the mother-plant for both regenerating and for the seedlings. The main factors influencing the development of the P. rigida species, limiting it to the clustered pattern are: 1) interspecific control; 2) wind action on terrain slopes; 3) light availability. The main interspecific controllers are: O. puberula, C. vernalis, M. umbellata and N. megapotamica. Even though, the seeds of P. rigida are wind-dispersed based on the wind strength to push, the wind action generates low pressure zones created by evergreen dense crowns from the higher and middle strata of the canopy which are obstacles to the seed dispersion of the species under study. When seeds reach the ground the other crowns do not let enough light through the canopy for the development of seedlings, thus the mortality rate was over 60% from the lower height class to the next. Therefore, the species P. rigida has all the essential conditions to be managed under the selection silvicultural system based on its natural regeneration and the stand to become a regular spatial pattern, once that interventions are carried out when under adequate silvicultural treatments, mainly, control thinning of the controller species and seedlings density of the population of P. rigida.